The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1073/pnas.85.16.6222
|View full text |Cite
|
Sign up to set email alerts
|

Atrial-specific granules in situ have high calcium content, are acidic, and maintain anion gradients.

Abstract: The composition and pH of atrial-specific granules of rat heart were determined by electron probe x-ray microanalysis and fluorescence microscopy, respectively. The high (75 mmol/kg of dry weight) calcium content and higher than cytoplasmic concentration of chloride in atrial-specific granules were visualized in high-resolution x-ray maps. The C1-content of granules and cytoplasm decreased and a bromide gradient (granule > cytoplasm) was established during incubation in low-chloride, NaBr-containing solutions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…In the present work, it was observed that the ASG contained high Ca content up to 81 mmol/kg dry wt., which approximates the value reported by Somlyo [18], and that Ca2+-ATPase was located on the membrane of ASG. Based on these findings, it is postulaled that the Ca2+-ATPase on the membrane of ASG may pump Ca2+ from cytosol (low Ca2+ concentration side) into ASG (high Ca2+ side) and, therefore, play a part in maintaining the high Ca concentration in the ASG.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In the present work, it was observed that the ASG contained high Ca content up to 81 mmol/kg dry wt., which approximates the value reported by Somlyo [18], and that Ca2+-ATPase was located on the membrane of ASG. Based on these findings, it is postulaled that the Ca2+-ATPase on the membrane of ASG may pump Ca2+ from cytosol (low Ca2+ concentration side) into ASG (high Ca2+ side) and, therefore, play a part in maintaining the high Ca concentration in the ASG.…”
Section: Discussionsupporting
confidence: 63%
“…Somlyo et al [18] reported a high Ca concentration in ASG and assumed it to be an ICaS. However, he did not explore how the high Ca concentration was maintained and whether the Ca stored in ASG participated in the ANP secretion.…”
mentioning
confidence: 99%
“…Our results further support the concept that acidocalcisomes are lysosome-related organelles and indicate that acidocalcisomes and serotonin-containing mast cell granules share several properties: they are acidic due to the operation of proton pumps and able to accumulate acidophilic dyes such as acridine orange; they can store large amounts of calcium and other cations such as potassium, sodium, magnesium, and zinc; they can release Ca 2ϩ in the presence of alkalinizing agents that also promote the hydrolysis of polyP; they contain large amounts of phosphorus in the form of polyP; and they have very high density when observed by direct electron microscopy. Other secretory granules, such as those in pancreatic islets of Langerhans (46), atrial specific granules (47), and secretory chromaffin granules (48) are known to possess large amounts of phosphorus and cations, as…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, Ca 2ϩ has also been reported to be present in acidic organelles carrying vacuolar-type proton pumps, such as endosomes, lysosomes, and the trans-Golgi network, and secretory granules such as chromaffin, pancreatic zymogen, and atrium-specific granules (19,37,50,61), but the functional significance of the high Ca 2ϩ content of these organelles is unknown (37). Recent evidence has indicated, however, that second messengers such as inositol 1,4,5-trisphosphate and cyclic ADP ribose can release Ca 2ϩ from pancreatic zymogen granules (19), although this conclusion is disputed by other investigators (57).…”
mentioning
confidence: 99%